2012
DOI: 10.2308/ajpt-50350
|View full text |Cite
|
Sign up to set email alerts
|

Audit Quality: Insights from the Academic Literature

Abstract: SUMMARY This study presents a review of academic research on audit quality. We begin with a review of existing definitions of audit quality and describe general frameworks for establishing audit quality. Next, we summarize research on indicators of audit quality such as inputs, process, and outcomes. Finally, we offer some suggestions for future research. The study should be useful to academics interested in audit quality as well as to the Public Company Accounting Oversight Board (PCAOB) and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
453
0
25

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 550 publications
(544 citation statements)
references
References 284 publications
16
453
0
25
Order By: Relevance
“…The PCAOB (2015a) stated that ''the hours that levels of an audit team devote to risk areas can suggest whether audit managers have staffed the audit appropriately to reflect the risk areas identified during the planning phase of the audit, and the extent to which senior members of the team have focused sufficiently on those areas.'' This position is supported by prior research indicating that higher audit budgets positively affect audit quality (e.g., see Knechel et al [2013] for a review). For example, research has indicated that time budget pressures may result in trade-offs of audit effectiveness for efficiency (McDaniel 1990) and increase the likelihood of reducing audit quality by acts such as signing off on audit workpapers prematurely, or failing to perform necessary audit steps (e.g., Alderman and Deitrick 1982;Kelley and Margheim 1990;Reckers, Wheeler, and WongOn-Wing 1997;Asare, Trompeter, and Wright 2000;Agoglia, Hatfield, and Lambert 2015).…”
Section: Fair Values and Audit Planningsupporting
confidence: 71%
See 2 more Smart Citations
“…The PCAOB (2015a) stated that ''the hours that levels of an audit team devote to risk areas can suggest whether audit managers have staffed the audit appropriately to reflect the risk areas identified during the planning phase of the audit, and the extent to which senior members of the team have focused sufficiently on those areas.'' This position is supported by prior research indicating that higher audit budgets positively affect audit quality (e.g., see Knechel et al [2013] for a review). For example, research has indicated that time budget pressures may result in trade-offs of audit effectiveness for efficiency (McDaniel 1990) and increase the likelihood of reducing audit quality by acts such as signing off on audit workpapers prematurely, or failing to perform necessary audit steps (e.g., Alderman and Deitrick 1982;Kelley and Margheim 1990;Reckers, Wheeler, and WongOn-Wing 1997;Asare, Trompeter, and Wright 2000;Agoglia, Hatfield, and Lambert 2015).…”
Section: Fair Values and Audit Planningsupporting
confidence: 71%
“…More specifically, the PCAOB stated that the amount and allocation of hours to various parts of the audit convey the effort put forth by the auditor, all of which are important inputs into audit quality. This position is supported by prior research (e.g., see Knechel, Krishnan, Pevzner, Shefchik, and Velury [2013] for a review). We propose that two key features fundamental to the auditing context-the framing of audit steps and the perceived verifiability of the performance quality of audit steps-may affect audit budgeting judgments.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, it is often argued that AQ is a difficult concept to define and it has been claimed that it is difficult to measure (Colbert & Murray, 1999;Francis, 2011;Knechel et al, 2013). However, it seems uncontroversial to state that AQ has to do with auditor effort (e.g.…”
Section: Theorymentioning
confidence: 99%
“…Research has shown that financial market participants reward companies that employ high-quality auditors (Barton, 2005;Knechel, Krishnan, Pevzner, & Stefchik, 2013). A necessary condition, however, is that the audit quality among audit firms can be differentiated.…”
Section: Recognition Of Peer Reviews and Inspections In Decision-makingmentioning
confidence: 99%